Automatic Fan Speed Controlled Laptop Cooling Pad System using Microcontroller - Indushan, S.; Ishara, M.; Buddhika, N. (IET Young Professionals' Technical Conference 2023 (IET YPTC), 2023)
A human way of life increasingly relies on automatic controls. The development of control techniques that boost system performance is the main goal of the large field of automatic control technology. The elimination of the human operator is the distinctive feature of automated control. The fan is one of these devices. The majority of fans come with speed controls, and the speed is adjusted according to the situation. Typically, a fan is run at a lower speed when the temperature is lower and at a higher speed when the temperature is higher. This is carried out manually by people. The fan speed is advised to be automatically controlled in this study in order to regulate a laptop's temperature. To automatically adjust the fan speed, a circuit comprising a brushless DC motor, DHT11 temperature sensor, Atmega328p microcontroller, and a few other electronic components is created and constructed. The temperature and fan speed are shown on LCD as an extra function. The developed system circuit is then tested several times and operated flawlessly
Keywords: Laptop cooling Pad; Atmega328p; DHT11; Fan Speed; BLDC motor; Circuit design